A Assessing Knowledge, Attitudes and Practices Related to Thalassemia: A Cross-Sectional Study Among University Students in Swat, Pakistan - Sumaia Saif; Mena Ibrahim; Murad Ali Rahat; Akhtar Rasool; Muhammad Israr (Kashmir Journal of Science)
Background & objectives: The most common and potentially fatal single-gene hereditary disorder affecting the manufacture of hemoglobin is thalassemia, which results from one or more globin chains fail to synthesize properly, either completely or partially. This disorder is prevalent worldwide in different regions including Pakistan. The relevance of the disorder necessitates that thalassemia and its prevention measures be widely known to the general public. This research sought to evaluate the perceptions and knowledge of thalassemia among Swat university students.